Do disarmament, demobilization and reintegration programs suffice in ‘rule of force’ environments: how to fill the security void? - Da Câmara Santa Clara Gomes, Sophie; Specker, Leontine (Revista Española de Desarrollo y Cooperación, 2023)
Disarmament, Demobilization and Reintegration (DDR) programs of ex-combatants are almost always carried out in complex (post) conflict political and security environments. The effectiveness and sustainability of DDR programs largely depend on such contextual factors, but are neither aimed nor capable of addressing them all. This paper aims at bringing attention to the need for a more holistic approach to DDR programs by strengthening the link with other peacebuilding initiatives with the objective to improve the Rule of Law, such as border control and community policing programs.